Medicinal plants used for diabetes and for dental problem in central part of Chhattisgarh, India. - Patel, D K (Journal of Phytology, 2012)
Utilization of herbal medicines over the world is increasing day by day due to their low side effect, minimum prize and for easily availability. There are many plants having potential values for treatment of varied diseases like Diabetes, Dental problem etc. Among the diverse Medicinal plants some are of remarkable potential for Diabetes and Dental problem which are focused in the current paper. India having around 45000 plant species, out of them many species of Medicinal plants are of rich potential for various diseases. Presence of the plants, traditional knowledge and mode of preparation are main factors leading to successful curing of the particular diseases. The present paper deals with the collection of information about the Medicinal plants used by local peoples from central parts of the Chhattisgarh state in India. Many Medicinal plants are utilized for various purposes. Out of them 30 and 25 plants were selected to document each problem as for Diabetes and for Dental problem. The observed plants are listed following their Botanical name, Common name, Family, Habit, Parts used, Mode of utilization and Propagation methods.